Estudos de pré-formulação e formulação de Heliotropium indicum (L.) DC (Boraginaceae) - COSTA, Russany Silva da (Universidade Federal do Pará, 2014)
Heliotropium indicum L. (Boraginaceae) is a shrub, reaches up to 70 cm high. It is known as “fedegoso” in the north and northeast of Brazil. Because of the biological potential of this species, this work aims to determine the quality parameters of the vegetable drug to the final product and evaluate the antimicrobial activity of the leaves of H. indicum L. The purpose of obtaining a phytotherapic formulation semisolid, we used the parameters of quality control physical, chemical and physicalchemical described in the Brazilian Pharmacopoeia and others literature. The vegetable drug was classified as coarse powder, showed values of loss on drying and total ash of 12.88% and 17.14%, respectively. The thermogravimetric analysis of the powder and the extract showed that both had good physical stability up to 180 °C. The spectra in the region IR showed an increase in the intensity of the absorption bands of the extract, which may relates to the extraction of chemical constituents of the cellular matrix. The prospecting chemical extract confirmed the presence of classes of secondary metabolites already reported in literature. The chloroform fraction suggests the presence of alkaloids by precipitation test with Dragendorff reagent. The TLC and HPLC showed a possible presence of the same substance in the alkaloidal and hexane fractions. The crude extract inhibited the growth of Staphylococcus aureus with halos of 12.5 mm ± 0.707 and 10.5 ± 0.707 mm for concentrations of 500 and 250 mg / mL, respectively. The physical mixtures of the extract with adjuvant pharmaceutical used to develop the phytotherapic formulation showed no physical incompatibility and no significant changes in the absorption profile of the compounds analyzed. The phytotherapic formulation semi-solid has a good stability after the preparation, after the submission of the gel by centripetal force and after the action of heat stress.